Probiotic application in freshwater prawns; some implication on farm profitability - Ramzani, Sara Ravan; Ismail, Mohd Mansor; Mohd. Daud, Hassan; Abdurofi, Ilmas (Scholars Research Library, 2014)
This study was done to determine the effects of periodical application of probiotics and pathogenic effects of A. hydrophila on the survival and growth enhancement of prawns. These prawns were individually weighed and kept in twenty one farms. Two trials were carried out. The first trial had seven feeding regimes designed asT1 (Control group); T2 (B. subtilisbacteriaonce every day), T3 (B. subtilis once every 5 day), T4 (B. subtilis once every 10 days), T5(Commercial Probiotic (CP) once every day), T6 (CP once every 5 days) and T7 (CP once every 10 days). The final concentration of the probiotic bacteria in the feeds was determined at 8 × 109 CFU/g feed. After 60 days of feeding, the prawns in each treatment were measured for growth performance. Then the prawns in each treatment were challenged with A. hydrophila at 107 CFU/mL for 21 days, and measurements for growth and survival rates were recorded at end of the challenge experiment. Parameters such as histopathology, bacteriological study, growth measurement and water quality were taken. Significant differences (P< 0.05) in weight gain, specific growth rate, feed intake and FCR between the treated B. subtilis and control groups were observed. Results showed a significant difference between control and treatments in the log of Bacillus count (Control: Mean = 1.40 ± 0.03, CPF; Mean= 4.10 ± 0.064, PF; Mean = 3.46 ± 0.084) and the log of gram negative count (Control; Mean= 3.29 ± 0.08, CPF; Mean = 1.91 ± 0.045, PF; Mean = 2.22 ± 0.059) (P < 0.001). Appropriate probiotic applications have been shown to improve intestinal microbial balance, thus leading to improved food digestion, and reduced pathogenic bacteria multiplication problems in the gastrointestinal tract and increase aquaculture production. Critical constraints in place and the main factors necessary for successful of aquaculture operation including social, economic, production technology as well as environmental aspects were considered for the future aquaculture development. The inland aquaculture checklist for Malaysia including, site selection, species source, business planning, environmental impact assessment and aquaculture licensing requirements was developed. This document provides information and assesses the main aspects required to develop and increase productivity an aquaculture project.